The importance of reliable social media information during the COVID-19 pandemic - Bernardino, Margarida (2022)
Bernardino, M., & Nicolau, L. B. (2020). The importance of reliable social media information during the COVID-19 pandemic. European Journal of Public Health, 30(Supl. 5). https://doi.org/10.1093/eurpub/ckaa165.067